2013
DOI: 10.1038/aps.2012.187
|View full text |Cite
|
Sign up to set email alerts
|

Norisoboldine alleviates joint destruction in rats with adjuvant-induced arthritis by reducing RANKL, IL-6, PGE2, and MMP-13 expression

Abstract: Aim: To explore the effects of norisoboldine (NOR), a major isoquinoline alkaloid in Radix Linderae, on joint destruction in rats with adjuvant-induced arthritis (AIA) and its underlying mechanisms. Methods: AIA was induced in adult male SD rats by intradermal injection of Mycobacterium butyricum in Freund's complete adjuvant at the base of the right hind paw and tail. From d 14 after immunization, the rats were orally given NOR (7.5, 15, or 30 mg/kg) or dexamethasone (0.5 mg/kg) daily for 10 consecutive days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…In our previous studies, the anti-migration activity of NOR was partially attributed to the prevention of the Notch1 pathway-related tip cell phenotype [11], [12]. In this study, preliminary experiments were conducted to examine the interplay between the PKA and Notch1 pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, the anti-migration activity of NOR was partially attributed to the prevention of the Notch1 pathway-related tip cell phenotype [11], [12]. In this study, preliminary experiments were conducted to examine the interplay between the PKA and Notch1 pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that NOR can inhibit VEGF-induced endothelial cell migration [11], [12]. To clarify whether this effect is related to the inhibition of the PKA pathway, the intracytoplasmic cAMP level and PKA activation in HUVECs were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The results of preliminary studies in our laboratory indicated that norisoboldine is a potential therapeutic agent for RA that functions by protecting joint destruction and inhibits synovial angiogenesis in the collagen II-induced arthritis of mice [13][14][15][16][17]. However, after a single intravenous administration of NOR to rats, the plasma concentrations of NOR sharply declined, followed by a slower phase of decrease until the levels fell below detection limits in 120 min [18].…”
Section: Introductionmentioning
confidence: 96%
“…However, under some pathological conditions, continuous addition of IL-6 has been shown to increase autoantibodies, such as anti-double-stranded DNA (anti-dsDNA) antibody production, making significant contributions to the inflammatory response and accelerating the progression of autoimmune diseases such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) [3][4][5] . A blockade of IL-6 or its receptor has been demonstrated to prevent elevated anti-dsDNA antibody levels and the progression of autoimmune diseases in addition to improving survival rates [6] .…”
Section: Introductionmentioning
confidence: 99%